The role of liver fat and insulin resistance as determinants of plasma aminotransferase elevation in nonalcoholic fatty liver disease. Issue 1 (25th November 2014) - Maximos, Maryann; Bril, Fernando; Portillo Sanchez, Paola; Lomonaco, Romina; Orsak, Beverly; Biernacki, Diane; Suman, Amitabh; Weber, Michelle; Cusi, Kenneth
<x xml:space="preserve">Abstract</x> Plasma aminotransferases (aspartate aminotransferase [AST] and alanine aminotransferase [ALT]) are usually increased in patients with nonalcoholic fatty liver disease (NAFLD). However, the factors behind their elevation remain unclear. The aim of this study was to assess the role of insulin resistance (IR) and liver triglyceride content in relation to histology in patients with NAFLD/nonalcoholic steatohepatitis (NASH) with normal or elevated ALT levels. To this end, we enrolled 440 patients, divided into three groups: no NAFLD (n = 60); NAFLD with normal ALT (n = 165); and NAFLD with elevated ALT (n = 215). We measured: (1) liver fat by proton magnetic resonance spectroscopy (1H‐MRS); (2) severity of liver disease by biopsy (n = 293); and (3) insulin sensitivity in liver, muscle, and adipose tissue by a euglycemic hyperinsulinemic clamp with 3‐3H‐glucose. Patients with NAFLD and elevated ALT, even when well matched for body mass index to those with normal ALT, had worse adipose tissue insulin resistance (ATIR; P < 0.0001), higher liver triglyceride content (P < 0.0001), and lower plasma adiponectin (P < 0.05), but no differences in hepatic insulin resistance. Similar results were found when only patients with NASH were compared: both ATIR (P < 0.0001) and liver triglyceride content by 1H‐MRS (P < 0.0001) were worse in NASH with elevated ALT. Consistent with the 1H‐MRS data, steatosis on liver biopsy was also significantly increased in patients with NASH and elevated ALT levels (P < 0.0001). However, and most important, there were no differences in inflammation (P = 0.62), ballooning (P = 0.13), or fibrosis (P = 0.12). Conclusion: In patients with NAFLD or NASH, ATIR (but not HIR) and liver triglyceride content are major factors in the elevation of plasma aminotransferase levels. Patients with normal versus elevated ALT had similar severity of NASH, suggesting that plasma aminotransferase levels are misleading parameters for guiding clinical management. (Hepatology 2015;61:153–160)